Sixteenth International Seaweed Symposium 1999
DOI: 10.1007/978-94-011-4449-0_44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper pollution on the ultrastructure of Lessonia spp.

Abstract: Plants of Lessonia trabeculata and L. nigrescens were studied by transmission electron microscopy in order to evaluate ultrastructural level changes in response to copper exposure. Samples of fronds, stipes, and holdfasts were collected from areas with and without copper mining discharges. Changes in cell ultrastructure observed in Lessonia trabeculata were related to copper concentrations in seawater, seaweeds and extracted alginates. The results strongly suggest that tolerance or adaptation of Lessonia to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The range of Cd in the eight species of macroalgae from the reference sites, including L. nigrescens, were higher than those reported for algae in non-upwelling areas (25-28) but were within the range reported for species within upwelling regions (12). On the other hand, the levels of Cu found in the study species were in agreement with values previously reported in macroalgae from different parts of the world (26,29,30). However, the high concentration of this metal measured in algae native to Caleta Palito, and in L. nigrescens transplanted for 2 months to this site, agree only with what has been reported in marine algae from other contaminated coastal systems (29,31,32).…”
Section: Discussionsupporting
confidence: 89%
“…The range of Cd in the eight species of macroalgae from the reference sites, including L. nigrescens, were higher than those reported for algae in non-upwelling areas (25-28) but were within the range reported for species within upwelling regions (12). On the other hand, the levels of Cu found in the study species were in agreement with values previously reported in macroalgae from different parts of the world (26,29,30). However, the high concentration of this metal measured in algae native to Caleta Palito, and in L. nigrescens transplanted for 2 months to this site, agree only with what has been reported in marine algae from other contaminated coastal systems (29,31,32).…”
Section: Discussionsupporting
confidence: 89%
“…The accumulation in S. lomentaria was not completely unexpected, as similar results have been reported for U. compressa, the only species that coexists in large densities with S. lomentaria at the copper-enriched site (Ratkevicius et al 2003) and for a variety of algae inhabiting metal-enriched coastal environments around the world (Foster 1976, Strömgren 1980, Luoma et al 1982, Ho 1984, 1990, Forsberg et al 1988, Say et al 1990, Mardsen and DeWreede 2000. The high levels of copper in the tissues of S. lomentaria naturally growing at the impacted site was not reflected in changes at the organellar level, as reported for other seaweeds such as Lessonia nigrescens (Leonardi and Vásquez 1999) and Enteromorpha flexuosa (Andrade et al 2004). This apparent absence of effects on the structure of the cells may well be the result of the attenuation of copper toxicity due to the scavenging activity of the antioxidant system of S. lomentaria, as discussed below.…”
Section: Discussionsupporting
confidence: 84%
“…2004). Intracellular copper accumulation was also revealed by accumulation of electron dense granules in various algal vacuoles from copper mine areas (Correa et al 1999;Leonardi and Vasquez 1999), where copper concentrations reach up to 6 mg L −1 (Castilla 1996) (similar to that in Cu3).…”
Section: Discussionmentioning
confidence: 84%